Grand Opening of New Fresno County Jail at M and Merced Streets - Watkins, Howard::::::::: (1989)
Sheriff Steve Magarian speaking; Seated: Supervisor Chair Vernon Conrad, Superior Court Presiding Judge Frank Creede, former Sheriff Hall McKinney and three others obscured